HUKUM WARIS ADAT SUKU “OSING “ DALAM PENYELESAIAN SENGKETA WARIS DI LUAR PENGADILAN DI DESA KEMIREN - Arie Ramadhani; Ikhwanul Qiram (MIZAN, Jurnal Ilmu Hukum, 2020)
Inheritance law that exists and applies in Indonesia, until now is still not a legal unification. Based on the inheritance map that is still so pluralistic, the result is that until now the regulation of inheritance issues in Indonesia is still not uniform. On the other hand, Customary Inheritance Law is an alternative settlement when the other two inheritance legal systems are unable to answer. Meanwhile, the settlement of inheritance disputes using the Customary Inheritance Law more fulfills a sense of justice from the community, especially in the Osing Tribe community. Aside from being more flexible because it follows the flow of change, it is also better at protecting the good name of the extended family because there are still many claims that inheritance disputes are a disgrace that must be kept confidential. The purpose of this study was to obtain a description of the norms of rules in the customary inheritance law of the osing tribe and the pattern of settlement of the dispute. The results of the study can be a picture of the existence and role of the osing customary inheritance in supporting the formation of positive law, especially in the region of Banyuwangi Regency based on local wisdom.